DAMPAK DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA CILELES KECAMATAN JATINANGOR KABUPATEN SUMEDANG - Andi Pitono; Kartiwi Kartiwi (ipdn, 2021)
ABSTRACT The study aims to analyze the impact of the Village Fund policy that has been implemented in Indonesia since 2015 on a community welfare. The Village Fund Study was conducted in Cileles Village, Jatinangor District, Sumedang Regency, West Java Province. This research design is a qualitative descriptive study. This research finds that the Village Fund policy is to pave the way for improving community welfare if it is managed in a transparent, accurate, reliable and organized manner. The meaning of the findings of this study leads to two things. First, a structural and legal mechanism is needed to ensure that communities are actively involved in the formulation of village fund policies, and that their voices are prioritized in village development planning. Second, good village financial management is as a first step towards increasing welfare. Keywords: Village Fund; Public welfare; Development Planning.